Efficient Polymer Solar Cells Based on Solution‐processed Vanadium Oxide as Hole‐extracting Layer. Issue 11 (14th November 2013) - Xiao, Biao; Cheng, Xiaoping; Zhao, Baofeng; Wu, Hongbin
Abstract Here we reported the fabrication of efficient polymer solar cells from regioregular poly(3‐hexylthiophene) (P3HT):fullerene derivative [6, 6]‐phenyl‐C61 butyric acid methyl ester (PC61BM) mixtures, in which solution‐processed vanadium oxide (VOx) was used as a hole‐extracting layer (HEL). The obtained devices exhibited a high power conversion efficiency of 3.96%, and can be enhanced to 4.06% and 4.16%, respectively, when two types of PEDOT:PSS with different conductivities were used in conjunction with the VOx layer. All the VOx‐based devices showed a high fill factor (FF) over 70%, which was ascribed to efficient hole extracting efficiency associated with the solution‐processed VOx hole‐extracting layer. The origins of the improvement were also studied by transmission spectra, atomic force microscope (AFM), and capacitance‐voltage characteristics.